HATE SPEECH ON MAUDY AYUNDA’S INSTAGRAM POST - Srikandi, Cut Novita; Safithri, Ajeng Meuthia (Universitas PGRI Sumatera Barat, 2024)
The advent of social media has facilitated convenience in daily living. In addition to exerting a positive influence, it is important to acknowledge that social media also has a detrimental impact. The emergence of negative repercussions is observed, notably through a surge in instances of linguistic crimes that yield detrimental outcomes. Language crimes encompass several forms of linguistic transgressions. This investigation falls within the domain of Forensic Linguistics. The objective of this research was to uncover instances of hate speech inside the comments section directed towards Maudy Ayunda in the G20 Speech Case on the Instagram News Feed. The feminist viewpoint was employed to examine the impact of societal patriarchal norms on the occurrence of hate speech directed towards Maudy Ayunda. This study employed a descriptive analysis methodology, utilizing data sources derived from comments made by netizens. The data was collected by examining the comments section of Instagram, and the author captured screenshots of selected comments for analysis. The results indicate that the dataset contains a total of ten instances of hate speech, which can be further categorized into eight instances of insults, one instance of blasphemy, and one instance of provocation. The study's findings indicate that individuals' opinions exhibit prejudice when it comes to influencing hate speech directed towards a female character.